Acute, chronic and acute/chronic ratio between starters and non-starters professional soccer players across a competitive season. (December 2022) - Nobari, Hadi; Castillo, Daniel; Clemente, Filipe Manuel; Carlos-Vivas, Jorge; Pérez-Gómez, Jorge
Quantifying the external training load across the season related to the starting status of players could be relevant for physical conditioning staff, since one of the main goals is to apply the adequate individual training load. Thus, the aims of this study were to (1) monitor the acute workload (wAW), chronic workload (wCW), and acute/chronic workload ratio (wACWR) on a weekly basis using the body load (BL) in starter and non-starter professional soccer players; and (2) analyze the differences between starters and non-starters for wAW, wCW, and wACWR using BL, and (3) analyze the weekly average of distance and sprint variables during four periods of the season (pre-, early-, mid-, and end-season). Twenty-one professional soccer players (28.3 ± 3.8 years; 181.2 ± 7.0 cm; 74.4 ± 7.7 kg) belonging to the same team competing in the Iranian Persian Gulf Pro League were evaluated for a period of 48 weeks (one soccer season). The season was divided into pre-season (weeks 1–5), early-season (weeks 6–19), mid-season (weeks 20–35), and end-season (weeks 36–48). Players were classified according to their starting status: players who were in the starting line-up (i.e. starters) and players who did not make the starting line-up (i.e. non-starters). The results showed greater weekly wAW and wCW for starters compared to non-starters during the mid-season (wAW: p  = 0.008, g  = −1.24; wCW: p  = 0.006; g  = −1.31) and end-season (wAW: p  = 0.001, g  = −1.66; wCW: p  = 0.001; g  = −1.62). Starters also showed greater weekly total distance (wTD), sprint total distance (wSTD), high-speed running distance (wHSRd), and repeated sprints compared with non-starters across all four periods ( p  < 0.05; g  = −1.36 to −4.95), higher wHSRd/wTD during pre-season ( p  = 0.007, g  = −1.28) and mid-season ( p  = 0.001, g  = −1.62) and a greater wSTD/wTD during pre-season ( p  = 0.029, g  = −0.99). Based on these findings, coaches and strength and conditioning specialists should individualize training according to match exposure throughout a competitive season.